Rheology of two-phase systems: A microphysical and observational approach. (August 2015) - Platt, John P.
Abstract: Ductile shear zones commonly contain distinctive bands of high strain rock characterized by intimately mixed fine-grained two-phase or polyphase material. These ultramylonite bands are weaker than the surrounding material, and may play a critical role in strain localization. How such zones develop, how the phases become evenly dispersed, the bulk rheology, and the controls on grain size, are all unclear. The following generic scenario may resolve some of these questions. 1) Dislocation creep and dynamic recrystallization cause grain-size reduction: commonly, the recrystallized grain sizes of the two phases differ. 2) Grain size reduction causes a switch to grain-boundary diffusion creep, which requires grain-boundary sliding. Diffusion allows one phase to fill spaces that open between grains of the other: this will happen most rapidly in the finer-grained phase. The grain size of the resulting mixture is therefore controlled by that of the finer-grained phase. This leads to mixing and dispersion of the two phases, producing a fine-grained, evenly dispersed two-phase aggregate. 3) The bulk rheology will be controlled by grain-boundary diffusion creep of the two phases, with the grain size controlled by the finer-grained phase. Bulk flow laws can be developed for quartz-feldspar and olivine-orthopyroxene ultramylonites based on these concepts, using appropriate mixing laws. Highlights: Phase mixing in ultramylonites occurs by grain-boundary sliding and diffusion creep. Grain size is controlled by dynamic recrystallization of the stronger phase. Rheology is controlled by diffusion creep in the weaker phase. Ultramylonites may deform up to four orders of magnitude faster than the protolith. Grain-size reduction and phase mixing are a powerful mechanism of strain localization.